A Superconcentrated Water‐in‐Salt Hydrogel Electrolyte for High‐Voltage Aqueous Potassium‐Ion Batteries. Issue 8 (18th February 2021) - Li, Yibo; Zhou, Zhuqing; Deng, Wenjun; Li, Chang; Yuan, Xinran; Hu, Jun; Zhang, Man; Chen, Haibiao; Li, Rui
Abstract: We report a high‐voltage aqueous full potassium‐ion battery (AFKIB) with a superconcentrated water‐in‐salt hydrogel electrolyte (WISHE). This WISHE exhibits an expanded electrochemical stability window (ESW) of 3.0 V as well as a high ionic conductivity of 4.34 mS cm −1 . The hydrogen bonds between the polymer network and the water phase help to further widen the ESW over a liquid‐type water‐in‐salt electrolyte, and prevent liquid leakage. The assembled AFKIB exhibits a considerable capacity of 135 mA h g −1 and a superior stability after 3000 cycles. This work provides a meaningful way of designing high‐voltage aqueous energy storage devices. Abstract : Make a WISHE : A superconcentrated water‐in‐salt hydrogel electrolyte (WISHE) is prepared for high‐voltage, aqueous, full K‐ion batteries, which exhibit outstanding cycling stability with high capacity. Such a WISHE provides a new strategy in aqueous electrolyte design for high‐voltage energy storage devices.